Health status measured by Kansas City Cardiomyopathy Questionnaire-12 in primary prevention implantable cardioverter defibrillator patients with heart failure - Gustav Mattsson; Marita Wallhagen; Peter Magnusson (BMC Cardiovascular Disorders, 2021)
Abstract Background Self-reported health status as measured by the Kansas City Cardiomyopathy Questionnaire (KCCQ) in patients with primary prevention implantable cardioverter defibrillators (ICDs) has mainly been reported from randomized trials. However, these studies are often limited to short follow-up and are subject to selection bias. The aim of this study was to assess KCCQ-12 in patients with primary prevention ICD due to either ischemic or nonischemic heart failure. Methods This cross-sectional observational study included all patients in Region Gävleborg, Sweden, who because of primary prevention due to heart failure, had an ICD or underwent device replacement between 2007 and 2017. After validation using medical records patients were sent and returned the KCCQ-12 by regular mail. Results A total of 118 questionnaires were analyzed (response rate 71.1%). The mean age was 70.9 ± 9.8 years, and a minority was female (n = 20, 16.9%). The mean overall summary score was 71.5 ± 22.4, there was no significant difference between ischemic and nonischemic heart failure (69.5 ± 23.1 vs. 74.4 ± 21.3; p = 0.195). Atrial fibrillation at baseline was associated with lower score for the domains Symptom frequency (70.2 ± 23.2 vs. 82.2 ± 19.2; p = 0.006) and Social limitation (62.1 ± 26.0 vs. 75.6 ± 26.6; p = 0.006) as well as the overall summary score (63.9 ± 21.3 vs. 74.8 ± 22.2; p = 0.004). Conclusion In a real-world setting, primary prevention ICD patients with heart failure report an acceptable disease-specific health status at long-term follow-up. Ischemic and nonischemic etiology showed similar health status whereas atrial fibrillation was associated with worse outcome.